Sistem Informasi Penjualan Ayam Asap Pada iSmoked Berbasis Web Menggunakan Metode RAD - Ranon Kusuma Chandra; Mohammad Iwan Wahyuddin (STMIK Budi Darma, 2022)
One of the foods of animal origin is chicken. Chicken is the animal that is most often consumed by humans, one of the processed chicken is smoked chicken. Smoked chicken is a product sold by iSmoked, iSmoked is located in the city of Jakarta, precisely on Jalan Manunggal II, South Petukangan. Because people rarely know about the existence of this smoked chicken shop and the rapid development of information systems entering the realm of business, therefore an information system is needed as a medium that can help solve shop owner problems. From the problems cited above, the purpose of this study is to build a sales information system that utilizes a website as a means of sales and promotion. This website was created using HTML and PHP programming languages and uses a framework, namely Codeigniter and Bootstrap so that the web display becomes responsive and attractive and can be opened on all types of browsers. The design of this information system uses the Rapid Application Development (RAD) method and the implementation of the test uses several methods such as interviews and system observations. With the design of this information system, the owner can sell their products with other media.